Race and the Fourth Amendment - Maclin, Tracey (1998)
In Whren v. United States, the Supreme Court held that pretextual traffic stops do not raise Fourth Amendment concerns. In this Article, Professor Maclin contends that by requiring only probable cause of a traffic offense to justify pretextual seizures, the Court mistakenly ignores racial impact when marking the protective boundaries of the Fourth Amendment. Professor Maclin argues that race matters when measuring the dynamics and legitimacy of certain police-citizen encounters. Pretextual traffic stops unreasonably use racial targeting, therefore, the Court should make racial impact a factor in determining the constitutionality of the pretextual seizure. Professor Maclin begins by examining objective, empirical evidence that police officers seize minority motorists for arbitrary traffic stops. Although Whren concluded that a police officer's subjective intentions are irrelevant, this evidence of racial targeting is more objective and reliable than other evidence the Court has sanctioned in Fourth Amendment analysis. The Article then turns to the Court's Fourth Amendment precedent, concluding that prior cases recognize the relevance of race, and that disparate racial impact is a proper consideration for Fourth Amendment analysis. Finally, the Article criticizes Whren because it fails to consider the real world of law enforcement and to reconcile that reality with a meaningful right to be free from unreasonable seizures. The Court ignores the fact that police discretion, police perjury, and the mutual distrust between black motorists and the police are issues intertwined with traffic enforcement. As a result, Whren assures that minority motorists will continue to feel like second-class citizens on the nation's roads